Building Trust and Reinforcing Democracy: Preparing the Ground for Government Action (OECD Public Governance Reviews, 2022)
Democracies are at a critical juncture, under growing internal and external pressures. This publication sheds light on the important public governance challenges countries face today in preserving and strengthening their democracies, including fighting mis- and disinformation; improving government openness, citizen participation and inclusiveness; and embracing global responsibilities and building resilience to foreign influence. It also looks at two cross-cutting themes that will be crucial for robust, effective democracies: transforming public governance for digital democracy and gearing up government to deliver on climate and other environmental challenges. These areas lay out the foundations of the new OECD Reinforcing Democracy Initiative, which has also involved the development of action plans to support governments in responding to these challenges.